Study on Energy‐Saving and Emission Reduction Solutions for the Bearing Heating System of Offshore Wind Turbines: A Case Study of General Electric's Offshore Wind Power Assembly Base - Huanrui Liang; Xiaoa Huang; Faquan Chen; Jiayang Wu; Leying Deng; Youxin Huang (Energy Science & Engineering)
ABSTRACT In the context of the global transition to renewable energy sources, the offshore wind power sector is confronted with operational inefficiencies during the thermal processing and assembly of wind turbine spindles and components. The research, centered on General Electric's offshore wind turbine assembly facility, addresses the deficiencies in the thermal management of bearing heating systems, the prevalence of rework due to substandard thermal treatments, and the inefficiencies in energy utilization. The paper proposes a targeted strategy comprising three key interventions: (1) The synchronization of bearing heating procedures with the off‐peak electricity tariff regime to mitigate peak demand and associated energy expenditures and carbon footprints. (2) The deployment of a thermoelectric generator (TEG) system to harness and convert waste heat into electrical energy, with meticulous modeling of its thermal dynamics. (3) The engineering of a thermally insulated housing for bearings to curtail thermal losses. The projected outcomes of these interventions are a reduction in electricity costs by 127.83 yuan, a decrease in carbon emissions by 90.41 kg, and a substantial reduction in heat loss. The findings of this research underscore the efficacy of thermal process optimization, waste heat recuperation, and thermal insulation in enhancing the energy efficiency of bearing heating systems, thereby contributing to the broader objectives of energy conservation and emission reduction in the renewable energy sector, which is imperative in the contemporary era of climate change mitigation and sustainable development.